Grinding temperature and power consumption in high speed grinding of Inconel 718 nickel-based superalloy with a vitrified CBN wheel - Dai, Chen-Wei; Ding, Wen-Feng; Zhu, Ye-Jun; Xu, Jiu-Hua; Yu, Hai-Wu (Precision engineering, 2018)
•High speed grinding of Inconel 718 superalloy was carried out using a vitrified CBN wheel.•Effects of wheel speed on grinding temperature and heat partition were determined.•Influences of wheel speed on grinding forces and specific grinding energy were investigated.•Power consumption in high speed grinding of Inconel 718 superalloy was provided.•High speed grinding generally produces precision surface of Inconel 718 superalloy. As a kind of typical difficult-to-cut metallic material, Inconel 718 nickel-based superalloy has been widely applied in aero-engines. High speed grinding experiments of Inconel 718 have been carried out using a vitrified cubic boron nitride (CBN) superabrasive wheel in the current study. The effects of wheel speed vs on grinding temperature and power consumption were investigated. Meanwhile, the grinding performance was also analyzed from the viewpoint of undeformed chip thickness. The results obtained show that, the minimum grinding forces and specific grinding energy are obtained at vs of 120m/s and the grinding temperature is less than 100°C at this moment. The lost grinding power reaches the maximum value when vs is 140m/s, which accounts for about 55%–65% of the total grinding power; however, the minimum values, such as about 20%–30%, are obtained at a conventional wheel speed. Finally, the wheel speeds in grinding Inconel 718 are optimized at 100–120m/s under the given experimental conditions, with which not only the surface roughness Ra below 0.4μm is obtained, but also the distorted lattice or elongated grain cannot be formed in the ground surface/subsurface layer.